2017
DOI: 10.18632/oncotarget.19521
|View full text |Cite
|
Sign up to set email alerts
|

miR-33a is a tumor suppressor microRNA that is decreased in prostate cancer

Abstract: Prostate cancer is one of the most frequently diagnosed neoplasms among men worldwide. MicroRNAs (miRNAs) are involved in numerous important cellular processes including proliferation, differentiation and apoptosis. They have been found to be aberrantly expressed in many types of human cancers. They can act as either tumor suppressors or oncogenes, and changes in their levels are associated with tumor initiation, progression and metastasis. miR-33a is an intronic miRNA embedded within SREBF2 that has been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 52 publications
(67 reference statements)
1
40
0
Order By: Relevance
“…The MiR‐33a is an intronic microRNA that resides within the 16 th intron of the SREBF2 gene with critical roles associated with regulation of lipid and cholesterol metabolism . It has also been reported as an important tumor suppressor in distinct tumor types through deregulating its targets' expressions . Our investigation of a recent dataset, in which microRNAs in CD133‐positive and CD133‐negative cells were profiled, demonstrated that miR‐33a expression in CD133‐positive cells, which were demonstrated to possess cancer stemlike features, is significantly lower compared to corresponding CD133‐negative cells, indicating a tumor suppressor function for miR‐33a.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The MiR‐33a is an intronic microRNA that resides within the 16 th intron of the SREBF2 gene with critical roles associated with regulation of lipid and cholesterol metabolism . It has also been reported as an important tumor suppressor in distinct tumor types through deregulating its targets' expressions . Our investigation of a recent dataset, in which microRNAs in CD133‐positive and CD133‐negative cells were profiled, demonstrated that miR‐33a expression in CD133‐positive cells, which were demonstrated to possess cancer stemlike features, is significantly lower compared to corresponding CD133‐negative cells, indicating a tumor suppressor function for miR‐33a.…”
Section: Discussionmentioning
confidence: 81%
“…14 It has also been reported as an important tumor suppressor in distinct tumor types through deregulating its targets' expressions. 13,[15][16][17][18][19][20][21] Our investigation of a recent dataset, in which microRNAs in CD133-positive and CD133-negative cells 24 were profiled, demonstrated that miR-33a expression in CD133-positive cells, which were demonstrated to possess cancer stemlike features, 34 is significantly lower compared to corresponding CD133-negative cells, indicating a tumor suppressor function for miR-33a. Cancer stem cells, resembling normal stem cells in their biologic features, are thought to be an important component of tumors, leading to cancer initiation, development, recurrence, invasion, metastases, and therapy resistance.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As such, PIM1 is regulated primarily by transcription, including induction by cytokines through the JAK/STAT pathway 5 and by hypoxia 6 . PIM1 protein levels are also regulated translationally via its 5' UTR 7 and by the microRNA miR-33a 8 . PIM1 has been implicated as an oncogene in both hematological malignancies, such as large B cell lymphoma 9 , and cancers of epithelial origins, such as breast and prostate cancer [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Ev idence suggests that approximately 60-90% of mRNA have the potential to be targeted by miRNA [8]. Recent studies have also suggested that miRNA may act as tumor suppressors in different cancers such as liver [9], colon [10], prostate [11] and bladder cancers [12].…”
Section: Introductionmentioning
confidence: 99%